A systematic approach to further improve stent-graft performance. (1st December 2021) - Liu, Zongchao; Teng, Shuai; Chen, Gongfa; Wu, Linhui; Yang, Junwei; Cui, Fangsen; Ho, Pei
Graphical abstract: Highlights: A new aortic arch stent-graft was designed based on the descending aorta stent-graft. The metal stent was coated with slit membrane in the new design. The new design improved the sealing effect between the stent-graft and aortic arch. Enough flow is able to enter into the side branches via the slits. Abstract: Thoracic endovascular aortic repair (TEVAR) is limited by the complicated anatomy of an aortic arch. This study proposed a new stent-graft (SG) design with slits that can positively improve the sealing effect between the aorta and SG while maintaining blood flow to supra-aortic branches. Firstly, a new SG was designed by changing the geometrical parameters (strut height, strut radius, strut diameter, etc.) based on previous research. The main mechanical performances of the SG were evaluated. Results showed that the new design improved the sealing effect and decreased the Type-Ι endoleak risk. The new design also had the comparable radial force, compression strength and fatigue life. Secondly, a fluid dynamic analysis was carried out in an ideal normal aortic arch model to evaluate the slit SG design. Satisfactory flow perfusion in branches was obtained, and no undesirable vortexes were found. Therefore, the hemodynamic environment in the aortic arch after the SG implantation was not significantly changed. The present study indicates that the design thought has a potential to deal with the technical difficulties of TEVAR at the aortic arch. This study provides the basis for potential optimization to obtain a more applicable SG design.